2017
DOI: 10.1016/j.triboint.2017.05.041
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soot and diesel contamination on wear and friction of engine oil pump

Abstract: The effect of oil contamination and oil degradation on friction and wear of engine oil pump are addressed in this paper. It provides a summary of an experimental study on the effects of oil contamination and oil degradation on tribological performance of a Variable Displacement Vane Pump (VDVP); a particular focus is on the vane-rotor contact. Firstly, a lab-based artificial ageing of fully-formulated engine oil (FFO) with the addition of contaminants such as carbon black (CB) and diesel is conducted. Secondly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Maintenance, in general, and the condition monitoring, in particular, aims to combine increase of reliability with the lowest costs possible, being direct or indirect. In this type of maintenance, Some relevant topics about related works on condition monitoring and predictive maintenance based on oil analysis, in urban buses fleets, are mentioned and discussed in [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance, in general, and the condition monitoring, in particular, aims to combine increase of reliability with the lowest costs possible, being direct or indirect. In this type of maintenance, Some relevant topics about related works on condition monitoring and predictive maintenance based on oil analysis, in urban buses fleets, are mentioned and discussed in [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…As it has been mentioned, those after treatment devices solve some of the emissions problems but compromise certain aspects related to the engine lubrication. The use of EGR lead to higher levels of soot in the engine oil [23,24] while the DPF regeneration process increases the oil degradation due to the raised temperatures inside the cylinder. In addition, the configuration of late fuel injections also tends to worsen the combustion stability and consequently, to increase both the soot levels in the combustion chamber and the fuel dilution in engine oil.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some differences in aggregate size and surface chemistry, Clague et al [34] found that similarities in the nanostructure enabled the surrogacy, at least for diesel soot. Motamen Salehi et al [35] used carbon black as substitute for diesel soot to assess the effect of engine oil pump wear. Studies by Mabuchi et al [36] used an analogous approach to investigate the wear of hydrogen-free diamond-like carbon coatings for engine applications.…”
Section: Introductionmentioning
confidence: 99%